Predicting the Risk from Cadmium Transfer to Crops from Soils Amended with Biosolids - McLaughlin, M.; Whatmuff, M.; Warne, M.; Heemsbergen, D.; Barry, G.; Bell, M.; Pritchard, Deborah; Penney, N. (Australian Water Association, 2007)
The National Biosolids Research Program (NBRP) has conducted field-based experiments throughout Australia over 4 years to determine the benefits and risks associated with biosolid applications onto agricultural land. The solubility and bioavailability of cadmium (Cd) in biosolids was assessed. Cadmium in biosolids was found to be quite soluble (equivalent to soluble Cd salts), but transfer to cereal grains was less than that indicated by solubility, due possibly to Zn or organic matter also added in the biosolids erducing Cd accumulation. Critical soil guideline values for Cd have been developed based on soil clay content and soil pH.